Loading and release of cancer chemotherapy drugs utilizing simultaneous temperature and pH-responsive nanohybrid - Mohammad Dahri; Hossein Akbarialiabad; Ahmad Miri Jahromi; Reza Maleki (BMC, 2021)
Abstract Background Recently, the development of nanocarriers and the improvement of their biochemical properties have became of great importance. Single-walled carbon nanotubes (SWCNT) have many applications in drug delivery systems (DDS) as a common carbon-based structure. In the current work, the penetration, co-loading, and co-release of Doxorubicin (DOX) and Paclitaxel (PAX), as two cancer chemotherapy agents, were investigated using a novel modified copolymer with functionalized SWCNT. Results This study proposes a dual-responsive smart carrier that is sensitive to pH and temperature. The carrier consists of functionalized SWNT and Dimethyl acrylamide-trimethyl chitosan (DMAA-TMC) grafting on SWCNT. This suggested carrier was investigated by utilizing molecular simulations. Interaction energies between DOX, PAX, and carrier as well as the affinity of drugs to the nanocarrier were studied. The energy analysis of drug release and adsorption presented that DOX and PAX delivery using this carrier is selective and sensitive at healthy and cancerous conditions. The attraction of DMAA-TMC, as a biodegradable and biocompatible copolymer, with SWCNT showed that degradation mechanism in acidic environment deformed the copolymer. This leads to a smart release mechanism in an acidic cancerous tissue. Additionally, it improves hydrophilicity, optimum nano-particle size, and cell cytotoxicity concerns. Conclusions The simulation results manifested a significant contribution of DMAA-TMC in the adsorption and release of cancer chemotherapy drugs in normal and neoplastic tissues. The interaction of copolymer also improves the biocompatibility and biodegradability of the SWCNT. Smart drug delivery carrier can be a valuable nanohybrid for loading, transporting, and releasing of cancer chemotherapy drugs. Graphical abstract